2017
DOI: 10.21776/ub.rjls.2017.004.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Urine Specific Proteins and Alpha-1 Antitrypsin Concentrations to Assess the Severity of Lupus Nephritis

Abstract: Current biomarkers for evaluating disease activity or severity in lupus nephritis (LN) are considered to be unsatisfactory. Pathological changes in glomerular basement membrane and selectivity of electrical discharge are causing specific patterns of urine proteins excretion. Together with alpha-1 antitrypsin (AAT), they are expected to become new biomarkers to assess LN activity.Seventy-one urine samples were collected from healthy controls and LN patients. Patterns of urine specific proteins were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
0
1
Order By: Relevance
“…~ 105 ~ This was in agreement with the results of research performed by Aggarwal et al [16] , in which median urinary ACT (uACT) levels were significantly higher in the active SLE group compared to all other groups (p< 0.001). In contrary to our findings, Susianti et al [15] observed no statistically significant correlation was found between cases with SLE activity and Urinary ALPH 1ACT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…~ 105 ~ This was in agreement with the results of research performed by Aggarwal et al [16] , in which median urinary ACT (uACT) levels were significantly higher in the active SLE group compared to all other groups (p< 0.001). In contrary to our findings, Susianti et al [15] observed no statistically significant correlation was found between cases with SLE activity and Urinary ALPH 1ACT.…”
Section: Discussioncontrasting
confidence: 99%
“…In our research, there was Strong positive significant correlation between urinary ALPH 1ACT, serum creatinine and 24HR urinary proteins, and (p<0.001). This was partially in agreement with the results of research performed by Susianti et al [15] , in which there was positive significant correlation between urinary ALPH 1ACT, serum creatinine and protein creatinine ratio. In our research, there was Strong positive significant correlation between cases with SLE activity and high Urinary ALPH 1ACT with r s =0.827 and (p<0.001).…”
Section: Discussionsupporting
confidence: 93%